HTML dog : the best-practice guide to XHTML & CSS - Griffiths, Patrick (New Riders, 2006)
For readers who want to design Web pages that load quickly, are easy to update, accessible to all, work on all browsers and can be quickly adapted to different media, this comprehensive guide represents the best way to go about it. By focusing on the ways the two languages--XHTML and CSS--complement each other, Web design pro Patrick Griffiths provides the fastest, most efficient way of accomplishing specific Web design tasks. With Web standards best practices at its heart, it outlines how to do things the right way from the outset, resulting in highly optimized web pages, in a quicker, easier, less painful way than users could hope for! Split into 10 easy-to-follow chapters such as Text, Images, Layout, Lists, and Forms, and coupled with handy quick-reference XHTML tag and CSS property appendixes, HTML Dog is the perfect guide and companion for anyone wanting to master these languages. Readers can also see the lessons in action with more than 70 online examples constructed especially for the book.